Phylogenetic relationship of phosphate solubilizing bacteria according to 16S rRNA genes - Nobandegani, Mohammad Bagher Javadi; Mohd Saud, Halimi; Wong, Mui Yun (Hindawi Publishing Corporation, 2014)
Phosphate solubilizing bacteria (PSB) can convert insoluble form of phosphorous to an available form. Applications of PSB as inoculants increase the phosphorus uptake by plant in the field. In this study, isolation and precise identification of PSB were carried out in Malaysian (Serdang) oil palm field (University Putra Malaysia). Identification and phylogenetic analysis of 8 better isolates were carried out by 16S rRNA gene sequencing in which as a result five isolates belong to the Beta subdivision of Proteobacteria, one isolate was related to the Gama subdivision of Proteobacteria, and two isolates were related to the Firmicutes. Bacterial isolates of 6upmr, 2upmr, 19upmnr, 10upmr, and 24upmr were identified as Alcaligenes faecalis. Also, bacterial isolates of 20upmnr and 17upmnr were identified as Bacillus cereus and Vagococcus carniphilus, respectively, and bacterial isolates of 31upmr were identified as Serratia plymuthica. Molecular identification and characterization of oil palm strains as the specific phosphate solubilizer can reduce the time and cost of producing effective inoculate (biofertilizer) in an oil palm field.